2012
DOI: 10.1136/bmjopen-2012-001274
|View full text |Cite
|
Sign up to set email alerts
|

Patient self-assessment of hospital pain, mood and health-related quality of life in adults with sickle cell disease

Abstract: IntroductionAcute pain is a hallmark of sickle cell disease (SCD) for which frequent hospital admissions may be required, affecting the quality of life of patients.ObjectivesTo characterise the relationship between adult patient self-reported sickle cell pain, mood and quality of life during and after hospital admissions.DesignLongitudinal study across three time-points.SettingSecondary care, single specialist sickle cell centre.Participants510 adult patients with SCD admitted to hospital daycare or inpatient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 16 publications
2
51
1
2
Order By: Relevance
“…Extant research has found that adolescents and young adults with SCD suffer from mild to moderate fatigue, and that high levels of fatigue are associated with increased depression, anxiety, stress, sleep disorder, chronic pain, and loss of activities of daily life and quality of life (11,34). Other research has found a relationship between pain and psychiatric disorder, and has demonstrated that reduced pain is associated with significant improvements in general health, quality of life, and mood disorder in SC patients (3,15). Bakri et al (10) found that patients with SCD and who had history of repeated hospitalization are at an increased risk of developing behavioral problems and psychiatric disorders, including depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Extant research has found that adolescents and young adults with SCD suffer from mild to moderate fatigue, and that high levels of fatigue are associated with increased depression, anxiety, stress, sleep disorder, chronic pain, and loss of activities of daily life and quality of life (11,34). Other research has found a relationship between pain and psychiatric disorder, and has demonstrated that reduced pain is associated with significant improvements in general health, quality of life, and mood disorder in SC patients (3,15). Bakri et al (10) found that patients with SCD and who had history of repeated hospitalization are at an increased risk of developing behavioral problems and psychiatric disorders, including depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the present study considered pain as a cause of acute fatigue, and the basic problem facing patients; pain management was therefore carried out as a central aim of the intervention. Extant research has argued that pain reduction may significantly improve general health, quality of life, mood disorder (15), and fatigue (11) in patients with SCD. This study's findings indicate that self-management programs may ameliorate fatigue, depression, anxiety, stress, and the frequency and duration of pain, in patients with SCD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pain is the main symptom of VOCs, and its management is still a challenge for hematologists, requiring a multidisciplinary approach . Although protocols for control of acute pain in SCD have been developed in the last decade, SCD patients still feel undertreated . Different mechanisms are involved in pain generation during VOCs: (i) the ischemic/reperfusion injury and activation of inflammatory response; (ii) the local release of sensitizing mediators, contributing to local vasodilation and edema; (iii) the neuropathic component sustained by an aberrant stimulation of central and peripheral nervous system .…”
Section: Introductionmentioning
confidence: 99%